Evaluasi Tingkat Pelayanan Simpang Fatmawati, Kota Semarang (Indonesian Journal of Civil Engineering Study, 2024)
Transportation is a means to support human activities and is also one of the pillars of economic growth. Economic growth also has an impact on population growth. Population growth affects the performance of traffic that occurs. The high traffic flow at Simpang Fatmawati occurs at each approach to the intersection, namely the approach from Brigjen Soediarto Street, the approach from Fatmawati Street, and the approach due Majapahit Street. The traffic performance at Simpang Fatmawati able to assess by reviewing the (LOS) or level of service that occurs. The assessment of the performance of Simpang Fatmawati can be done using the Indonesian Road Capacity Guidelines (2023) method, with results such as intersection capacity, degree of saturation, queue length, number of stopped vehicles, and delays that occur. Furthermore, based on the degree of saturation results, the Level of Service (LOS) of Simpang Fatmawati can be determined. Referring to the analysis results, at the approach from Brigjen Soediarto Street, the queue length is 284 meters. At the approach from Fatmawati Street, the queue length is 272 meters. While at the approach from Majapahit Street, it is 425 meters. At the approach from Brigjen Soediarto Street, the Degree of Saturation (DS) value is 1.09. At the approach from Fatmawati Street, a value of 1.32 is obtained. Meanwhile, at the approach from Majapahit Street, the Degree of Saturation (DS) reaches a value of 2.3. Based on the Degree of Saturation (DS) value and the queue length, the Level of Service of Simpang Fatmawati can also be determined to be at level (F).
Keywords: Junction Performance; Degree of Saturation; Queue Lengt